Optical element in-vivo sampling grating and preparation method thereof

By using femtosecond laser to prepare the sampling grating inside the fused quartz component, the problem of reducing anti-laser damage performance caused by surface contaminants is solved, and efficient and precise grating preparation is achieved, ensuring efficient measurement of the sampling beam and the integrity of the component surface.

CN119644490APending Publication Date: 2025-03-18HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411889581.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing sampling gratings are prepared on the surface of fused quartz components, and chemical films are required to be applied, resulting in residual surface contaminants and reduce anti-laser damage performance.

Method used

The sampling grating is prepared inside the large-diameter fused quartz component. Through optimized design and parameter adjustment of the femtosecond laser, the functional modification of the grating is achieved to avoid contamination caused by the surface coating.

Benefits of technology

The laser damage resistance of the sampling grating is improved, and efficient measurement of the sampling beam is ensured. It has high processing accuracy and low thermal effect, which does not affect the integrity of the component surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119644490A_ABST
    Figure CN119644490A_ABST
Patent Text Reader

Abstract

The invention discloses an in-vivo sampling grating of an optical element and a preparation method thereof, relates to the technical field of optical engineering, and aims to solve the problems that the existing sampling grating is prepared on the surface of a fused quartz element, and chemical films with different functions need to be coated on the surface of the grating, so that pollutants on the surface of the sampling grating are easy to remain; and the problem of laser damage resistance of the sampling grating is reduced. Comprising the following steps: S1, designing a grating structure, preparing a sampling grating on the surface of an optical element in the element through optimization design, and designing line pair, period and duty ratio parameters of the sampling grating in the element according to parameter requirements of the sampling grating; s2, cleaning the large-diameter fused quartz optical element, and fixing the large-diameter fused quartz optical element on a processing platform; s3, adjusting the wavelength of femtosecond laser, focusing a light spot into the element, and performing internal modification processing according to designed grating parameters; and S4, adjusting the focusing light spot to move in the element, and scanning and modifying in the element by using a specific line pair to obtain the in-vivo sampling grating of the large-aperture fused quartz element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optical engineering technology, and in particular to an in-vivo sampling grating of an optical element and a preparation method thereof. Background Art

[0002] A large number of fused silica optical elements are required in the optical path of a giant laser device. Among them, the sampling grating used at the optical path terminal is the "eye" of the laser system. It can provide accurate laser parameters by sampling the light beam in the laser system, and provide accurate laser parameter measurement results for each subsystem, which can comprehensively and effectively guarantee the stable operation of the laser device. The sampling grating is the last optical element in the high-energy ultraviolet laser system. It measures the total laser energy by diffracting and focusing a small part of the total laser energy. The sampling grating is suitable for the full wavelength range and can be used for sampling large-aperture light beams. It provides a sampling beam for the main laser energy measurement without affecting the main beam. In order to maintain the main laser energy, the diffraction efficiency of the sampling grating is specified to be 1‰~3‰. In addition, the sampling efficiency of the sampling grating is less than 5%.

[0003] At present, holographic lithography-ion etching technology is mainly used to directly prepare large-size sampling gratings. However, the sampling efficiency uniformity of the prepared sampling gratings cannot meet the requirements of strong laser systems. Some scholars have proposed to improve the sampling efficiency uniformity of sampling gratings based on chemical mechanical polishing methods. However, in the preparation process, the sampling efficiency uniformity and laser damage threshold are both difficult points that need to be paid attention to for sampling gratings. At present, the sampling gratings are prepared on the surface of fused quartz elements, and chemical films with different functions are also coated on the grating surface, resulting in residual contaminants on the surface of the sampling grating, which reduces the anti-laser damage performance of the sampling grating. Summary of the invention

[0004] The technical problems to be solved by the present invention are:

[0005] The existing sampling grating is prepared on the surface of a fused quartz element, and chemical films with different functions need to be coated on the grating surface, which can easily lead to residual contaminants on the surface of the sampling grating, thereby reducing the sampling grating's resistance to laser damage.

[0006] The present invention adopts the following technical solutions to solve the above technical problems:

[0007] The present invention provides a method for preparing a sampling grating in an optical element, comprising the following steps:

[0008] S1. Design a grating structure, prepare the sampling grating on the surface of the optical element inside the element through optimization design, and design the line pair, period and duty cycle related parameters of the internal sampling grating according to the parameter requirements of the sampling grating;

[0009] S2, cleaning the large-aperture fused quartz optical element and fixing it on the processing platform;

[0010] S3, adjust the wavelength of the femtosecond laser, focus the light spot inside the component, and perform internal modification processing according to the designed period and duty cycle;

[0011] S4. Adjust the focus spot to move inside the element, and scan and modify it with a specific line pair inside to obtain a sampling grating inside the large-aperture fused quartz element.

[0012] Furthermore, the line pairs of the sampling grating in S1 are 20001 / mm, the duty cycle is 50% to 100%, and the period is 1 to 3 μm.

[0013] Furthermore, the wavelength of the femtosecond laser in S3 is 1030nm and the pulse width is 255fs.

[0014] Furthermore, the single pulse energy of the femtosecond laser in S3 is 0.1 to 1.5 μJ.

[0015] The present invention provides an internal sampling grating of an optical element prepared by the method described in the above technical solution.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention proposes to use a femtosecond laser to prepare a sampling grating inside a large-aperture fused quartz element, and to use the femtosecond laser to modify the inside of the fused quartz element, thereby changing the diffraction rate of the fused quartz element and realizing the function of the sampling grating. It has the following advantages: (1) The femtosecond laser can be directly focused on the inside of the element, and directly act on the material inside the fused quartz element to realize local modification of the fused quartz element; (2) The modified area of ​​the femtosecond laser is stable. The modification of the femtosecond laser is mainly determined by multi-photon ionization, and its power density reaches the ionization threshold only in a very small area around the center of the spot. Therefore, the irradiation modification range of the material is stable; (3) The processing accuracy is high. The femtosecond laser breaks the diffraction limit with its ultrashort pulses, and can perform ultra-fine modification on the inside of the material at the sub-micron or even nanometer scale, which can effectively guarantee important parameters such as the sampling grating centerline density, sampling efficiency uniformity and projection efficiency; (4) The thermal effect is small. The femtosecond laser The pulse width is much smaller than the energy relaxation time, so the lattice is not affected by the electroacoustic interaction and heated up. The temperature in the action area will not increase significantly, and the thermal effect of damage can be ignored. (5) Femtosecond laser processing technology does not require strict environmental factors. There is no chemical reagent and sample contamination involved in the preparation process, and it is widely applicable to a variety of dielectric transparent materials. (6) Femtosecond laser processing of the sampling grating inside the fused quartz element will not damage the surface of the fused quartz element, and the laser damage resistance of the fused quartz element will not change. At the same time, since there is no grating structure on the surface, even if the surface of the element is coated, there will be no contaminants that affect the laser damage performance, thus ensuring the laser damage resistance of the sampling grating. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a schematic diagram of a processing system in an embodiment of the present invention;

[0019] Figure 2 Schematic diagram of a working method of a sampling grating in an optical element body in an embodiment of the present invention;

[0020] Figure 3 Schematic diagram of the processing trajectory in an embodiment of the present invention;

[0021] Figure 4 2 is a processing device and a light path diagram in an embodiment of the present invention. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, exemplary implementations or embodiments of the present invention will be described below in conjunction with the accompanying drawings. Obviously, the described implementations or embodiments are only implementations or embodiments of a part of the present invention, not all of them. Based on the implementations or embodiments of the present invention, all other implementations or embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present invention.

[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0024] The present invention provides a method for preparing a sampling grating in an optical element, comprising the following steps:

[0025] S1. Design the grating structure, prepare the sampling grating on the surface of the optical element inside the element through optimization design, and design the line pair, period and duty cycle related parameters of the internal sampling grating according to the parameter requirements of the sampling grating.

[0026] The present invention designs the structural parameters of the in-vivo sampling grating according to the sampling grating parameter requirements in an actual high-power laser device and the femtosecond laser modification process parameter requirements. During the processing of the sampling grating, there may be an error between the theoretical calculated value and the actual processed value.

[0027] The existing sampling grating parameters are mainly a center line density of 2000l / mm, a surface grating groove depth of several tens of nanometers, and a period of 1 to 3μm. Therefore, the present invention designs a volume sampling grating based on the grating diffraction theory. To achieve the same effect, the center line density of the volume sampling grating is 2000l / mm, and the grating groove width is regulated by the grating duty cycle. A sampling grating with a duty cycle of 50% to 100% is prepared and its key parameters such as the first-order transmission efficiency and sampling efficiency are tested.

[0028] According to the grating scalar diffraction theory, the grating period is Λ. Assuming that the amplitude transmittance of a single period is a function f(x), the grating transmittance function is:

[0029]

[0030] in represents convolution, comb represents comb function, and Fourier transform is performed to obtain:

[0031]

[0032] in Λ represents the grating constant. When a plane wave of unit amplitude is incident on the grating vertically, the above formula is used to analyze the diffraction efficiency of the sampling grating.

[0033] S2. Clean the large-aperture fused quartz optical element and fix it on the processing platform.

[0034] like Figure 1 and Figure 4As shown, the processing device includes a laser part and a machine tool part, wherein the laser part includes a laser and its computer and water cooling device, and an infrared femtosecond laser optical path; the machine tool part includes a computer, an XYZ processing platform, a galvanometer system, and a CCD camera. The in vivo sampling grating is modified and prepared inside the fused quartz element by the laser processing device. Turn on the laser, control the computer, the water cooling device, and the processing platform, adjust the laser optical path so that the infrared laser with a wavelength of 1030nm enters the processing platform, adjust the laser frequency to 20KHz, and the single pulse energy to 2μJ to process a "cross" on the silicon wafer for focus determination.

[0035] S3. Adjust the wavelength of the femtosecond laser, focus the light spot inside the component, and perform internal modification processing according to the designed period and duty cycle.

[0036] The processing parameters are shown in Table 1.

[0037] Table 1

[0038]

[0039]

[0040] When an infrared femtosecond laser acts on fused silica, a large number of free electrons are generated in the material in a very short time through photoelectric action. Although the free electron density is far less than that of conductors and metals, it is sufficient for the free electrons within the skin depth to directly absorb the femtosecond laser energy. After absorbing the energy, the electrons transfer the energy to the lattice system for electroacoustic coupling. The photoelectric action stage and the electroacoustic action stage occur in a very short time. The two-temperature equation (Formula (3) and (4)) is used to describe the above process. The electron action time is much shorter than the action time between the electron and the lattice. The drastic energy changes in the material are mainly concentrated in the electronic system. Therefore, the energy lost in the phonon action process can be ignored. At the same time, assuming that there is no energy exchange between the fused silica and the surrounding environment, the energy coupling model is expressed as:

[0041]

[0042] Where C e is the electron heat capacity, C l is the lattice heat capacity, T e is the electron temperature, T l is the lattice temperature, K e is the electronic thermal conductivity, g is the electroacoustic coupling coefficient, I effis the laser source term. According to the action mechanism of femtosecond laser and fused silica material in formula (3) and formula (4), the single pulse energy parameter range of femtosecond laser processing modification process is 0.1~1.5μJ. In order to precisely control the degree of femtosecond laser modification so as to optimize the passband rate and sampling efficiency of the sampling grating, the critical electron density parameter theory is introduced to calculate the parameters of different femtosecond laser energies, repetition frequencies, scanning speeds, spot overlap rates and track overlap rates. Multi-factor orthogonal experiments are carried out to explore the optimal process parameters of femtosecond laser modification preparation of volume sampling gratings. The wavelengths are determined to be 355nm ultraviolet laser and 1030nm infrared laser. During the experiment, it is found that the pass rate of fused silica material for ultraviolet laser is too high, so that the laser energy absorption is less and it cannot cause large-scale modification inside the fused silica material, and it cannot be used to prepare volume gratings. However, infrared laser can effectively improve the performance of fused silica material. Under the action of high peak power, the femtosecond laser and the fused quartz material produce nonlinear absorption, which affects the free electron density of the fused quartz material and causes material modification. Therefore, a 1030nm infrared femtosecond laser is used to modify the fused quartz material to prepare an in vivo sampling grating. Experimental verification is carried out on the single pulse energy range of 0.1 to 1.5μJ, and it is found that when the single pulse energy is below 1μJ, the degree of material modification is small and the grating preparation function cannot be achieved. When the single pulse energy is greater than 1.5μJ, the material is ablated and cannot meet the requirements. Therefore, the single pulse energy is controlled between 0.1 and 1.5μJ.

[0043] When the femtosecond laser acts on the material, the focal plane of the femtosecond laser appears at different depths of the material, and the absorption depth of the laser by the material will change accordingly. This embodiment assumes that the femtosecond laser is incident vertically on the surface of the fused quartz element, so the equivalent laser heat source term I total It is expressed as:

[0044] I total =I peak ·f space ·f time (5)

[0045] Where I peak is the peak power density, f space is the distribution function in space, f time is the distribution function over time.

[0046] It is believed that the femtosecond laser has Gaussian distribution in both time and space. peak 、f space 、f time It is expressed as:

[0047]

[0048] f space =exp[-2(ω s / ω) 2] (7)

[0049]

[0050] Where F is the energy density, t p is the pulse width, ω is the beam waist radius, ω s is the distance from the center of the focal spot. When the femtosecond laser interacts with the material, it first undergoes the interaction between the femtosecond laser photons and the material electrons. The electrons absorb the photon energy to form free electrons. When the free electron density exceeds the critical density, the basic properties of the material will change. At this time, a large amount of plasma is generated inside the material. In order to obtain a complete sampling grating in the body, the free electron density and plasma density need to be precisely controlled, otherwise the plasma will splash and cause material damage. Based on the two-temperature equation, the energy transfer process in the process of femtosecond laser modification of fused quartz material is determined, and the femtosecond laser modification of fused quartz material experiment is further designed.

[0051] After the above operation, adjust the laser to emit an infrared femtosecond laser with a wavelength of 1030nm, a pulse width of 255fs, a repetition rate of 300KHz, and a single pulse energy of 1μJ, and set the scanning speed to 50mm / s. After refocusing, adjust the laser parameters to a laser frequency of 300KHz, focus the femtosecond laser spot inside the component, and perform internal scanning modification on the component. The diffraction index of the modified fused quartz component changes, and the laser beam is separated from the main beam to achieve laser off-axis focusing and sampling, such as Figure 2 shown.

[0052] In order to achieve a first-level transmission efficiency of 0.1-0.3% for the sampling grating, a center line density of 2000l / mm and a modified line width of micrometer level, the energy distribution of the femtosecond laser is precisely controlled in the time and space domains, so that the energy of the rear spot inside the femtosecond laser focusing element is accurately distributed, effectively controlling the modification range.

[0053] S4, such as Figure 3 As shown, the focused spot is adjusted to move inside the element, and a specific line pair is scanned and modified inside the body to obtain a sampling grating inside the large-aperture fused quartz element.

[0054] The modified in vivo sampling grating of femtosecond laser is affected by comprehensive factors. Energy, repetition frequency, scanning speed and other factors will change the repair structure from different aspects of microscopic morphology, width, diameter and shape. In order to achieve the best primary transmission efficiency and ensure the surface accuracy and laser damage threshold of optical components, the scanning trajectory during the femtosecond laser modification process is precisely controlled. The response surface method is used to regulate the moving speed and repetition frequency of the laser during the scanning modification process. The combination of the two can achieve perfect concentric grating processing while ensuring the surface integrity of the optical component. There is a certain correlation between the various motion parameters, and the trajectory overlap rate G yand the spot overlap rate G x , which can be expressed as:

[0055]

[0056] Among them, r0 is the focal radius of the light spot, d x Spot overlap distance, d x =v s / f,d y Track overlap distance. In order to better prepare the in vivo sampling grating, the spot overlap rate and track overlap rate need to be strictly controlled.

[0057] The track overlap rate needs to be adjusted according to the designed sampling grating parameters, mainly based on formula (10) and grating parameter design; the track overlap rate is directly related to the repetition frequency and scanning speed, as shown in formula (9). Therefore, in order to reduce energy accumulation and improve processing efficiency, high repetition frequency and high scanning speed are adopted.

[0058] The large-aperture sampling grating provides a sampling beam for laser energy measurement without affecting the main beam. The in vivo sampling grating prepared by femtosecond laser internal modification is experimentally measured by using an optical path system for measuring sampling efficiency. According to the above characteristics of the sampling grating, the performance of the sampling gratings prepared with different parameters is evaluated using the experimental system of sampling efficiency and first-order diffraction efficiency. The gratings under test are detected by lasers of different wavelengths. The incident light is vertically incident on the grating under test, and the first-order diffraction light intensity is measured by the detector. By changing the wavelength of the incident light, the diffraction efficiency of the first-order diffraction light at the corresponding wavelength is measured. Then the prepared sampling grating is tested for its anti-laser damage performance using a self-built laser damage test system. The gratings under test are tested using the R-on-1, S-on-1, and 1-on-1 test methods, and their laser damage thresholds are statistically calculated.

[0059] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a sampling grating in an optical element, characterized in that: The steps include: S1. Design a grating structure, prepare the sampling grating on the surface of the optical element inside the element through optimization design, and design the line pair, period and duty cycle related parameters of the internal sampling grating according to the parameter requirements of the sampling grating; S2, cleaning the large-aperture fused quartz optical element and fixing it on the processing platform; S3, adjust the wavelength of the femtosecond laser, focus the light spot inside the component, and perform internal modification processing according to the designed period and duty cycle; S4. Adjust the focus spot to move inside the element, and scan and modify it with a specific line pair inside to obtain a sampling grating inside the large-aperture fused quartz element.

2. The method for preparing a sampling grating in an optical element according to claim 1, characterized in that: The line pairs of the sampling grating in S1 are 2000l / mm, the duty cycle is 50% to 100%, and the period is 1 to 3μm.

3. The method for preparing a sampling grating in an optical element according to claim 2, characterized in that: The wavelength of the femtosecond laser in S3 is 1030nm and the pulse width is 255fs.

4. The method for preparing a sampling grating in an optical element according to claim 3, characterized in that: The single pulse energy of the femtosecond laser in S3 is 0.1 to 1.5 μJ.

5. A sampling grating inside an optical element prepared by the method described in claim 1.

Citation Information

Patent Citations

  • Method for preparing waveguide grating in transparent dielectric material

    CN101055332A

  • Method for preparing bragg grating by femtosecond laser and apparatus

    CN101359067A

  • Method for preparing geometric phase optical element in sapphire by using femtosecond laser

    CN112792451A

  • Femtosecond laser ablation method for ultra-precision fused quartz element

    CN118875500A